2013
DOI: 10.1103/physreva.87.015401
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of cross sections to the diffuseness of the confining potential in time-dependent close-coupling calculations of the double photoionization of He@C60

Abstract: Calculations of the photoionization of endofullerenes often use a square-well potential to represent the confining fullerene. The sensitivity of the photoionization cross sections to the form of this model potential is explored here by the use of a diffuse potential. The cross sections for single photoionization with excitation and double photoionization of He@C 60 are found to show damping of the confinement resonance structure as the degree of diffuseness is increased using a commonly adopted well depth of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The corresponding HF equation is then solved in order to determine the wavefunctions and electron elasticscattering phase shifts upon e + A@C 60 collision. Note that this approximation, where the C 60 is modeled by the the potential U c (r) with the atom A being at the center of the potential, has been used for the study of the interaction of photons and charged particles with endohedral fullerenes A@C 60 on numerous occasions to now, see, e.g., [1,4,[9][10][11][12] (and references therein). Also, the replacement of the C 60 cage by the same potential U c (r) was employed in work [13] for the study of electron elastic scattering off empty C 60 as well.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding HF equation is then solved in order to determine the wavefunctions and electron elasticscattering phase shifts upon e + A@C 60 collision. Note that this approximation, where the C 60 is modeled by the the potential U c (r) with the atom A being at the center of the potential, has been used for the study of the interaction of photons and charged particles with endohedral fullerenes A@C 60 on numerous occasions to now, see, e.g., [1,4,[9][10][11][12] (and references therein). Also, the replacement of the C 60 cage by the same potential U c (r) was employed in work [13] for the study of electron elastic scattering off empty C 60 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Spectra of A@C 60 endohedral fullerenes, where the atom A is being encapsulated inside the hollow interior of the C 60 cage, have attracted a great deal of attention of researchers. To date, primarily photoionization spectra of various atoms A from A@C 60 systems have been detailed theoretically at various levels of sophistication (see, e.g., review papers [1,2] as well as some recent works on the subject [3,4,5,6] and references therein) and, to a lesser extent, experimentally [7,8]. Some insight has also been gained by theorists into other basic phenomena of nature occurring in A@C 60 , such as Auger vacancy decays [9,10,11] and fast charged-particle impact ionization reaction [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar potential, initial state correlations in Be and Mg have been studied [76]. The sensitivity of the double photoionization cross section from He@C 60 to the diffuseness of the model potential has been studied [77] employing a combination of the Wood-Saxontype potentials. It was shown that confinement resonance structures are damped as the degree of diffuseness increased.…”
Section: Model Potentialsmentioning
confidence: 99%